2018
DOI: 10.1080/09546634.2017.1422591
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the efficacy and safety of the interleukin (IL)-12/23 and IL-17 inhibitors ustekinumab, secukinumab, ixekizumab, brodalumab, guselkumab and tildrakizumab for the treatment of moderate to severe plaque psoriasis

Abstract: Ustekinumab, secukinumab, ixekizumab, brodalumab, guselkumab, and tildrakizumab were highly efficacious and generally well-tolerated when used as treatments for moderate to severe plaque psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
111
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 46 publications
0
111
0
3
Order By: Relevance
“…Systematic reviews suggest that agents targeting IL-17 may be more effective than those targeting IL-23 in patients with moderate to severe plaque psoriasis and that ixekizumab ranks among the most effective of the anti-IL antibodies. [4][5][6][7] Reviewing similar evidence based on clinical trials, NICE concluded that ixekizumab was more clinically effective than adalimumab and ustekinumab, and agreed it was likely that ixekizumab was comparable with secukinumab and infliximab, in terms of the proportion of patients achieving a 75% reduction in the Psoriasis Area and Severity Index score (PASI 75 response) after 12 weeks' treatment. 2 Direct comparative trials with ustekinumab (n=302) 8 and etanercept (two studies involving a total of 2570 patients, though not all received the licensed dose) 9 in patients with moderate to severe psoriasis have been published.…”
Section: Efficacymentioning
confidence: 99%
“…Systematic reviews suggest that agents targeting IL-17 may be more effective than those targeting IL-23 in patients with moderate to severe plaque psoriasis and that ixekizumab ranks among the most effective of the anti-IL antibodies. [4][5][6][7] Reviewing similar evidence based on clinical trials, NICE concluded that ixekizumab was more clinically effective than adalimumab and ustekinumab, and agreed it was likely that ixekizumab was comparable with secukinumab and infliximab, in terms of the proportion of patients achieving a 75% reduction in the Psoriasis Area and Severity Index score (PASI 75 response) after 12 weeks' treatment. 2 Direct comparative trials with ustekinumab (n=302) 8 and etanercept (two studies involving a total of 2570 patients, though not all received the licensed dose) 9 in patients with moderate to severe psoriasis have been published.…”
Section: Efficacymentioning
confidence: 99%
“…Further studies comparing treatments are ongoing or awaiting publication, including guselkumab vs. secukinumab (phase 2, NCT03553823; phase 3, NCT03090100) and vs. ixekizumab (phase 4, NCT03573323) and risankizumab vs. secukinumab (phase 3, NCT03478787). In addition, three recent meta‐analyses have assessed the safety of IL‐23p19 inhibitors compared with other classes of biologic agents used for the treatment of psoriasis . To avoid risk of confounding, these meta‐analyses exclusively used data from the placebo‐controlled treatment periods of randomized controlled trials (typically 12–16 weeks).…”
Section: Other Safety Datamentioning
confidence: 99%
“…The second meta‐analysis assessed the efficacy and safety of IL‐23p19, IL‐12/23p40 and IL‐17 inhibitors in moderate to severe plaque psoriasis and included data from 24 trials involving 15 388 patients . Safety outcomes included the number of patients with at least one AE, with at least one SAE and withdrawing from therapy because of an AE at 12–16 weeks.…”
Section: Other Safety Datamentioning
confidence: 99%
See 2 more Smart Citations